Bangladesh Climate Research: The Role of IRBs - Md. Matiur Rahman; Mohammad Mahbub Ur Rahim; Md. Anup Rahman Chowdury; Md. Abdul Mazid; Md. Amirul Islam; Md. Kaoser Bin Siddique (Bangladesh Journal of Bioethics)
This review examines the critical role of Institutional Review Boards (IRBs) in facilitating ethical climate change and health research in Bangladesh, a nation highly vulnerable to climate-sensitive diseases. The inadequacy of reliable health impact data, coupled with disparities in public perception of climate change risks influenced by socioeconomic factors, underscores the urgency for ethically sound research. This study systematically reviewed peer-reviewed journals, conference papers, institutional reports, and policy documents published within the last decade, focusing on ethical challenges in climate studies and the function of IRBs. Thematic analysis revealed key areas: the paramount importance of research ethics (including informed consent and privacy), the multifaceted impacts of climate change and adaptation strategies, the complexities and challenges faced by IRBs (especially in developing countries), the critical consideration of vulnerability in research participants, the issue of corruption in adaptation efforts, and the necessity of effective stakeholder engagement. The findings emphasize the interconnectedness of ethical principles, climate change challenges, and institutional responsibilities, advocating for interdisciplinary approaches. The review concludes by highlighting the need to strengthen the capacity of Ethical Review Committees, promote stakeholder engagement, integrate ethics into climate change policies, prioritize addressing vulnerability, and enhance institutional integrity to ensure equitable and sustainable solutions in Bangladesh.